Debating difference : group rights and liberal democracy in India - Bajpai, Rochana, 1972- (New Delhi : Oxford University Press, 2011)
How can inequalities between groups be addressed, while at the same time sustaining common citizenship? Debating Difference offers a new approach to this key question for liberal democracies, demonstrating that argument and debate is crucial for reconciling the demands of group equality and civic unity. Using constitutional and legislative debates on minority rights and quotas in Indian parliament, Rochana Bajpai develops a model for interpreting group rights aroundsecularism, democracy, social justice, national unity, and development.
Includes bibliographical references (pages [296]-310) and index.
Keywords: Ethnic relations; India -- Ethnic relations; Minorities -- Civil rights -- India